Holidays & celebrations. (RDA Enthusiast Brands, LLC, 2015)
"From Independence Day picnics and poolside parties to Halloween haunts and Christmas Eve buffets, great times are moments away with the all-new Tast of Home Holidays & Celebrations at your fingertips,"--page [4] of cover.